2002
DOI: 10.1091/mbc.e02-05-0292
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Modulates Matrix Contraction via Focal Adhesion Kinase– and Rho-mediated Signaling Pathways

Abstract: A provisional matrix consisting of fibrin and fibronectin (FN) is deposited at sites of tissue damage and repair. This matrix serves as a scaffold for fibroblast migration into the wound where these cells deposit new matrix to replace lost or damaged tissue and eventually contract the matrix to bring the margins of the wound together. Tenascin-C is expressed transiently during wound repair in tissue adjacent to areas of injury and contacts the provisional matrix in vivo. Using a synthetic model of the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 55 publications
3
130
0
Order By: Relevance
“…Statistical analysis showed that fTn-C expression is associated with liver metastases of pancreatic cancers. These findings are in accordance with the reports from Midwood and co-workers (16,17). Moreover, in these metastatic cancers, fTn-C formation was associated with MMP-2 activation, suggesting that MMP-2 may contribute to Tn-C organization.…”
Section: Discussionsupporting
confidence: 92%
“…Statistical analysis showed that fTn-C expression is associated with liver metastases of pancreatic cancers. These findings are in accordance with the reports from Midwood and co-workers (16,17). Moreover, in these metastatic cancers, fTn-C formation was associated with MMP-2 activation, suggesting that MMP-2 may contribute to Tn-C organization.…”
Section: Discussionsupporting
confidence: 92%
“…Almost all known binding sites lie in the fibronectin type III repeats or the fibrinogen globe, but evidence has been reported suggesting that the EGF-like repeats act as low affinity ligands for EGF receptors (15). As a consequence, cell interactions with tenascin-C are quite complex, and several signaling mechanisms have been identified, including recent observations that tenascin-C blocks focal adhesion kinase-and Rho-mediated signaling pathways activated by fibronectin (2,16,17) as well as stimulating Wnt and other growth-promoting pathways (18). For a detailed discussion of these mechanisms, please refer to Gertrude Orend's recent review (4).…”
Section: About the Familymentioning
confidence: 99%
“…Tenascin-C not only interacts with other ECM molecules, such as perlecan and fibronectin, but also cellsurface receptors including integrins a2b1, avb3 and a9b1, annexin II, and syndecan (40). It is proposed that the inhibition of syndecan-4, Rho, and FAK in cell spreading and the fibronectin matrix assembly by tenascin-C are major mechanisms for cell detachment operating in solid tumors (41,42). However, T lymphocytes express little syndecan-4 (43,44).…”
Section: Discussionmentioning
confidence: 99%